Dataset from RNAseq analysis of differential gene expression in germinal vesicle and metaphase I stages of granulosa cellsNational Center for Biotechnology Information - Weijun Gong; Xiangqian Meng; Ping Lei; Penghao Li; Jing Li; Yan Zhu (Data in Brief)
We present transcriptomic data on human granulosa cells, which are essential parts of reproductive biology. These data consisted of single-cell transcriptomic data from 12 biological samples from two developmental stages (germinal vesicle and metaphase I). We evaluated these data by calculating gene expression profiles at different developmental stages and detected differences in gene expression in granulosa cells at the different developmental stages. We further evaluated the transcriptomic data via genomes from gene banks. Thus, these new data demonstrate the feasibility of obtaining reliable transcriptomic data from individual samples at different developmental stages, and provide a framework for systematic transcriptomic studies of granulosa cell development.